Vitality of Lembak Language Bengkulu City in the Dynamics of Contemporary Society - Andriadi, Andriadi; Sarwono, Sarwit (Masyarakat Linguistik Indonesia Universitas Andalas, 2024)
This study explored the current situation and challenges facing the preservation of the Lembak language among the Lembak ethnic group in Bengkulu City. With globalization and modernization, there were concerns about keeping indigenous languages like Lembak alive, especially with the influence of dominant languages. The study aimed to evaluate the vitality of the Lembak language, identify factors contributing to its preservation or decline, and provide recommendations for its sustained maintenance amid the continuously changing societal dynamics. Employing a mixed-method approach, the methodology encompassed cluster sampling for a survey comprising 210 respondents drawn from seven neighborhoods across three districts in Bengkulu City, alongside purposive sampling for interviews involving 36 respondents from diverse demographic strata encompassing varying age groups and occupational backgrounds, including parents, teachers, and students, all of whom were native Lembak speakers. Findings revealed an average vitality index of 0.38 for the Lembak language, signifying its endangered status. While the language remained prevalent among older age groups limited in their community, its usage notably declined among younger generations, partially due to language contact and a preference for dominant languages. This situation is exacerbated by the lack of formal support and promotion from the government, absence of official backing, insufficient formal teaching materials, minimal language documentation, and the necessity for the Lembak language to adapt to the new challenges of the digital era to remain relevant and develop.To ensure the Lembak language survives, it was suggested to raise awareness, improve education, and gain support from the government and other groups.